Pengaruh Kreativitas dan Inovasi terhadap Kewirausahaan - Putri, Indry Anggraini; Nawawi, Zuhrinal M. (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
The approach of writing this article is to use descriptive analytic to analyze the impact of creative and innovative ideas on the world of business entrepreneurship. The data collection technique is the search for secondary data obtained from sources relevant to the topics discussed. By applying this concept, you will have a great opportunity to face the challenges that exist and have great potential in facing today's increasingly fierce business competition. Businessmen will be unable to compete with similar businesses if they do not take advantage of these creative and innovative ideas and the products marketed will not attract consumers so that the business they run will experience a decline. Therefore, the existence of this idea will have a considerable impact on the economy and the business world so that consumers do not get tired of buying and using these products. However, consumers can feel satisfied because they can use a product with many benefits that can be utilized by consumers Keywords : entrepreneurship, creativity, innovation